Hiring family or non-family managers when non-economic (sustainability) goals matter? A multitask agency model - Jenny Kragl; Alberto Palermo; Guoqian Xi; Joern Block (Small Business Economics, 2023)
Nepotism, altruism, lower managerial abilities, and a small pool of qualified family candidates may speak against family management. However, a large share of family-owned firms is run by family managers. Our study develops a theoretical model that provides an explanation for this paradox, linked to the multitasking problem of managing economic and non-economic tasks in family firms. Comparing the performance of family and non-family managers under moral hazard and imperfect performance measurement, we find that incentive pay leads to an effort distortion towards economic outcomes for both manager types, however less so for family managers. This effort distortion is less pronounced when economic and non-economic management tasks are complements. We show that family managers with excellent skills regarding non-economic goals of the owner family often outperform non-family managers even if they have poor skills in economic tasks or, what is more, if they have lower average abilities altogether. We further show that the interdependence between economic and non-economic goals in the manager's job tends to have a moderating effect on the family manager's relative performance. Our study contributes to the literature about family management and agency costs in family firms and has practical implications for family firms' hiring decisions. By highlighting the importance of non-economic goals, it moreover adds to the current discussion about the compliance with firms' sustainability goals.
Keywords: D82; D86; M12; M21; M52; M54; 330; Family firms; Family management; Manager selection; Multitask model; Incentives; Non-economic goals; Sustainability; Expertise